Study on the practices nonlinear optics with AGS and ZGP crystals - Sh. Alnayli, Raad (Al-Qadisiyah Journal of Pure Science, 2019)
In thispaperby means of the new method known as Å½-Scan technique, the nonlinear optical properties for Zink Germanium Di phosphate ZnGeP2 and Sliver Gallium Selenite (AgGase2) have been studied . Å½-scan experience was doneby laser called Nd-yag at 532 nm and 1064 nm and output of (80,40 ,35 and 25) mW, in two parts. The first one was a closed-aperture placed ahead of the detector to calculate the index of nonlinear refractive. While the second part; the aperture ahead the detector was taken away (open manhole) to calculatethecoefficient of nonlinear absorption. The experiential outcomes exhibit that the Sliver Gallium Selenite (AgGaSe2) exhibits positive refractive index (self-focusing) and saturation absorption, while the experimental results for Zink Germanium Di phosphate ZnGeP2 exhibits negative nonlinear refraction(self-defocusing)and two-photon absorption.